Termites (Blattodea: Isoptera) of Canada, continental USA, and Mexico: an identification key to families and genera, checklist of species, and new records for Mexico - De Luna, Manuel; Rudolf H., Scheffrahn; García-Barrios, Roberto; Cuellar-Rodriguez, Gerardo (Instituto de Ecología, A.C., 2023)
An illustrated identification key to the North American termite families and genera based mainly on the soldier caste is proposed. A checklist of termites (Insecta: Blattodea: Isoptera) of Canada, continental USA and Mexico is presented, listing 89 species (and two subspecies) grouped in 26 genera and four families. Five species are added to the Mexican termite fauna, these records are for the states of Campeche: Cryptotermes cavifrons; Quintana Roo: Cryptotermes cavifrons, Neotermes holmgreni, Neotermes phragmosus, Neotermes mona; Sonora: Incisitermes banksi; and Yucatan: Neotermes phragmosus. Other 32 new state records are made for the states of Aguascalientes, Baja California Sur, Campeche, Chiapas, Jalisco, Nuevo Leon, Oaxaca, Quintana Roo, Sonora, and Yucatan. The species Coptotermes crassus, Coptotermes havilandi, Incisitermes perparvus, Microcerotermes strunckii, Nasutitermes costalis, Incisitermes nigritus and Termes melindae are eliminated from the termite fauna of this region.